Modified Rammsonde tests in layered compacted snow - Feng, Zhuang; Peng, Lu; Zhijun, Li; Hongwei, Han; Wei, Li (Polar Research Institute of China - PRIC, 2019)
Investigation of the physical and mechanical properties of snow has long been a topic of interest to researchers as the construction of compacted-snow runways in Antarctica developed. In an attempt to assess the strength of layered compacted seasonal snow, penetration tests using modified Rammsonde were conducted in Harbin, China in early 2018. Compared with previous models, the modified Rammsonde is lighter overall, with improved resolution; thus, it is more suitable for seasonal snow; the mechanical structure was adjusted, and the reading of depth data is more convenient. A total of 74 penetration tests were carried out and the results were analyzed both qualitatively and quantitatively. The results of these analyses demonstrated the applicability of the device, and revealed that several factors affect the cone penetrometer’s estimate of the strength of the layered compacted seasonal snow. Such factors include the confining pressure, penetration energy, and the snow material properties, particularly the compaction of the snow undergoing penetration. A linear relationship between the penetration pressure and snow density was also established. The effect of age hardening on the penetration pressure was studied and the microstructure of the snow particles was observed through a microscope. These analyses showed that the cone penetrometer and data processing methodology applied in this study enable a rapid estimate of strength in seasonal snow, and may be applied in Antarctica after further modification. This would provide a scientific basis for the design of China’s Antarctic ice sheet airport.